ANALISIS PENGARUH PENDAPATAN PERKAPITA, KURS, PENGANGGURAN, POPULASI DAN REMITANSI TERHADAP MIGRASI INTERNASIONAL DI INDONESIA TAHUN 2014-2022 - Noni Milenia Jewel; Sitti Retno Faridatussalam (JURNAL ILMIAH EDUNOMIKA, 2024)
Indonesian Migrant Workers (PMI) carrying out international migration is an alternative chosen by the community to overcome problems in their areas of origin such as poverty, low income, job opportunities that are difficult to obtain. This shows that there is quite a serious problem with employment, namely that the available workforce cannot be properly absorbed in Indonesia. This research aims to determine the influence of per capita income, exchange rate, unemployment, population and remittances on international migration in Indonesia in 2014-2022. This type of research is quantitative research and the method used is a panel data regression model with data taken from 12 countries where Indonesian migrant workers are placed, namely Hong Kong, Taiwan, Malaysia, South Korea, Japan, Singapore, Saudi Arabia, Italy, United Arab Emirates, Qatar , Turkey, and Kuwait (cross section) in the period 2014-2022 (time series). The research results show that the Fix Effect Model (FEM) was chosen as the best model with the exchange rate variable having a positive effect on international migration while the variables per capita income, unemployment, population and remittances have a negative effect on international migration in Indonesia in 2014-2022. Keywords : International Migration, Indonesian Migrant Workers, Economic Development, Employment, Job Opportunities